The Effect of RME-Learning Trajectory on Mathematical Reasoning Ability and Self-Efficacy in Learning Statistics Using Congklak Games - Al Firdaus, Nabila Uristu; Usodo, Budi; Kuswardi, Yemi (Universitas Ahmad Dahlan, 2024)
This research aims to determine whether there is an effect of learning trajectory with the traditional congklak game context on mathematical reasoning ability in terms of self-efficacy. This study adopts a quasi-experimental approach using a 2 × 3 factorial design. The target population included all eighth-grade students at SMP Negeri 2 Wonogiri. The research employed cluster random sampling, selecting learners from two classes. The data collection techniques used were documentation, self-efficacy questionnaire, and mathematical reasoning abilities test. This study employed a data analysis approach that involved a two-way analysis of variance. The results of the hypothesis testing concluded that (1) learners who were taught using an RME-based learning trajectory with the traditional congklak game context showed better mathematical reasoning abilities compared to those taught through direct learning in statistics; (2) learners with high self-efficacy have better mathematical reasoning abilities than those with moderate or low self-efficacy, while learners with moderate self-efficacy showed better mathematical reasoning abilities than those with low self-efficacy; (3) there was no significant interaction observed between the treatment and self-efficacy regarding learners' mathematical reasoning abilities.